Osteopetrosis, Hypophosphatemia, and Phosphaturia in a Young Man: A Case Presentation and Differential Diagnosis. (9th February 2012) - Mitri, Zahi; Tangpricha, Vin
Abstract : We report the case of a 30-year-old African-American male with osteopetrosis and hypophosphatemia, presenting with diffuse myalgias. Laboratory evaluation performed revealed a low serum phosphorus level with urinary phosphate wasting, low calcium, and 25-hydroxyvitamin D concentrations, as well as elevated alkaline phosphatase. Skull and pelvic radiographs revealed high bone density consistent with high bone mass found on bone mineral density reports. PHEX gene mutation analysis was negative. Patient was started on calcium and phosphorus replacement, and he clinically improved. This paper will review the different subtypes of osteopetrosis, and the evaluation of hypophosphatemia.